1999
DOI: 10.1165/ajrcmb.21.5.3749
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide (NO) Upregulates NO Synthase Expression in Fetal Intrapulmonary Artery Endothelial Cells

Abstract: Endothelium-derived nitric oxide (NO) generated by endothelial NO synthase (eNOS) is critically involved in pulmonary vasodilation during cardiopulmonary transition at birth. Inhaled NO therapy has recently been considered for patients with persistent pulmonary hypertension of the newborn (PPHN). To better understand the mechanisms regulating NO synthesis in the developing pulmonary circulation and the possible ramifications of NO therapy, studies were performed with early passage ovine fetal intrapulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
2
18
2
Order By: Relevance
“…Our findings that eNOS protein abundance remained at control levels in both arteries and airways of preterm lambs that received iNO during mechanical ventilation, however, are consistent with the previous report that NO donors increased NOS expression in cultured pulmonary artery endothelial cells derived from fetal sheep (47). Preservation of vascular eNOS, however, yielded no significant benefit with respect to either PVR or arterial smooth muscle abundance.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings that eNOS protein abundance remained at control levels in both arteries and airways of preterm lambs that received iNO during mechanical ventilation, however, are consistent with the previous report that NO donors increased NOS expression in cultured pulmonary artery endothelial cells derived from fetal sheep (47). Preservation of vascular eNOS, however, yielded no significant benefit with respect to either PVR or arterial smooth muscle abundance.…”
Section: Discussionsupporting
confidence: 91%
“…The latter result surprised us because diminished eNOS is sometimes used to explain the apparent elevation of pulmonary vascular resistance that frequently occurs when iNO therapy is discontinued. On the other hand, our surprising finding is consistent with the results of in vitro studies, which showed that NO donors increase NOS expression in cultured pulmonary artery endothelial cells derived from fetal sheep (202).…”
Section: Evolving Neonatal Cld Leads To Increased Hydrostatic Pulmonasupporting
confidence: 92%
“…42 However, incubation of lamb fetal intrapulmonary artery endothelium with L-NAME decreased, and exogenous NO increased, eNOS activity, protein, and mRNA levels. 43 Despite the high L-NAME concentration used in the latter study (2 mmol/L), these contradictory findings could result from the different cell types studied. Our results of higher eNOS mRNA and protein and lower eNOS activity could represent an adaptive response of HUVECs from IUGR pregnancies to a reduced NO level.…”
Section: Casanello Et Al Iugr Inhibits Endothelial L-arginine/no Pathwaymentioning
confidence: 83%